Public-private partnerships for health: their main targets, their diversity, and their future directions - Widdus Roy (The World Health Organization, 2001)
The global burden of disease, especially the part attributable to infectious diseases, disproportionately affects populations in developing countries. Inadequate access to pharmaceuticals plays a role in perpetuating this disparity. Drugs and vaccines may not be accessible because of weak distribution infrastructures or because development of the desired products has been neglected. This situation can be tackled with push interventions to lower the costs and risks of product development for industry, with pull interventions providing economic and market incentives, and with the creation of infrastructures allowing products to be put into use. If appropriately motivated, pharmaceutical companies can bring to partnerships expertise in product development, production process development, manufacturing, marketing, and distribution - all of which are lacking in the public sector. A large variety of public-private partnerships, combining the skills and resources of a wide range of collaborators, have arisen for product development, disease control through product donation and distribution, or the general strengthening or coordination of health services. Administratively, such partnerships may either involve affiliation with international organizations, i.e. they are essentially public-sector programmes with private-sector participation, or they may be legally independent not-for-profit bodies. These partnerships should be regarded as social experiments; they show promise but are not a panacea. New ventures should be built on need, appropriateness, and lessons on good practice learnt from experience. Suggestions are made for public, private, and joint activities that could help to improve the access of poor populations to the pharmaceuticals and health services they need.